Corporate strategies and tax avoidance: Does corporate social responsibility matter? - Sismanyudi, Deddy; Firmansyah, Amrie (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2022)
This study aims to empirically analyze the effects of corporate diversification, customer concentration, and related party transactions (RPTs) on tax avoidance. In addition, we analyze the role of corporate social responsibility (CSR) disclosure in moderating the impacts of these independent variables on tax avoidance. We test the hypotheses on Indonesian listed manufacturing firms in 2014-2019, resulting in 414 firm-year observations. Our non-moderated multiple linear regression analyses reveal that corporate diversification and customer concentration are positively associated with tax avoidance, while RPTs do not affect tax avoidance. However, the moderated regression analysis reveals that CSR disclosure strengthens (weakens) the positive effect of corporate diversification and RPTs on tax avoidance. Overall, our results indicate the nuanced role of CSR activities. Specifically, firms can use CSR to conceal their tax management activities but also to act ethically to benefit their stakeholders.